Japanese and South Korean environmental aid: What are their life stories? - Aki Tonami; Anders Riel Müller (Danish Institute for International Studies (DIIS), 2013)
Environmental aid has become a major component of foreign aid, as environmental degradation and climate change have arisen as global concerns. Japan contends it has committed itself to the protection of the global environment since the 90s, and environmental aid has been an important part of that effort. South Korea has recently become an emerging actor in the development aid community and has also started to market its green diplomacy through programs such as the Global Green Growth Institute. Meanwhile, both Japanese aid and Korean aid have been criticized for being driven by their economic interests rather than altruism and that they focus too strongly on infrastructure projects. Against this background, we aim to analyze and compare Japanese and Korean environmental aid to shed light on the influence that emerging agents of aid such as South Korea can bring to the political dynamics and the overall governance of environmental aid. In our analysis, we refer to the definition of Williams (2002), which regards aid policy as an 'autobiography' of donor countries. Using an 'autobiography' approach we examine five elements of Japanese and Korean environmental aid: The bureaucratic and institutional imperatives, the internal procedures and processes, the stated policies, the practices and particular attitude that underlie them, and the broader impulse behind aid. By moving away from an altruistic/self-interest dichotomy, this analysis seeks to understand autobiographic trajectories of Japanese and Korean environmental aid rather than to evaluate them.
Keywords: 300